Nutrition in immune balance (NIMBAL) therapy : using diet to treat inflammatory bowel disease - Suskind, David L. (Nimbal Publishing LLC, 2016)
Each year thousands of kids and adults are diagnosed with inflammatory bowel disease (IBD) in the form of ulcerative colitis and Crohn's disease. The incidence of IBD continues to rise, and a major culprit is our food environment. Our diets affect our fecal microbiome, the trillions of bacteria that naturally reside in our digestive tract. What we eat changes the type of bacteria within the microbiome and can cause them to get out of balance and trigger our immune system to attack our bowels. But nutrition and diet are frequently overlooked in medicine and science. Nutrition in Immune Balance.